ChemInform Abstract: Hexaaquanickel(II) Dihydrogen Hypodiphosphate. Issue 9 (4th March 2014) - Gjikaj, Mimoza; Wu, Peng; Pook, Niels‐Patrick
Abstract Single crystals of the title compound are precipitated from a solution of Ni(OH)2 and H4P2O6.